(M, N)-Double-Framed Soft bi-Ideals of Abel Grassmann's Groupoids - Izhar Muhammad; Khan Asghar; Farooq Muhammad; Hila Kostaq (Discussiones Mathematicae - General Algebra and Applications, 2022)
The left invertive law makes Abel Grassmann's groupoids (briefly AG-groupoids) a very interesting structure to study. In this paper, we define (M, N)-double-framed soft bi-ideals (briefly (M, N)-DFS bi-ideals) and (M, N)-double-framed soft generalized bi-ideals (briefly (M, N)-DFS generalized bi-ideals) of AG-groupoids and study some of its properties. We obtain some interesting results of these notions in intra-regular AG-groupoids.